Assistance in the Implementation of Inclusive School Policy in Sekaran 02 State Elementary School - Fatma Kusuma Mahanani; Sukma Adi Galuh Amawidyati (Educational Psychology Journal, 2023)
The implementation of inclusive school policies is increasingly being carried out by various schools, especially public schools which are designated as pilot inclusive schools by the government. However, not all schools are ready to face various needs in implementing inclusive schools. One of them is SD N Sekaran 02 which still needs assistants and training for various teacher competencies in teaching inclusive schools. The activities to be carried out are training in the initial identification of children with special needs and training in the preparation of individual learning designs for children with special needs. The subjects in this study were 9 elementary school teachers. The research design uses one group design with pretest and post-test. The instruments used in this study were the teacher efficacy scale and the RPI knowledge test. Data analysis used Wilcoxon signed rank test analysis with statistical software JASP version 14.0. The results of the analysis showed that the inclusion policy implementation assistance program was effective in increasing teacher knowledge (p<0.05) and teacher efficacy (p<0.05).